Sign languages for all: teaching and interculturality - Lovón , Marco (2024)
Sign languages are natural and native languages. In recent years they have gained importance in the university context in the area of research, development of materials, and academic events. Some research groups have been created and are dedicated to their grammatical, pedagogical or technological study. The aim of this paper is to give an account of the academic work on the dissemination, teaching and interculturality of sign languages. To this end, the following events are highlighted: 1) the International Congress of Sign Languages held in Peru, 2) the thematic dossier on sign languages, 3) LSP (Peruvian Sign Language) in Peruvian universities, and 4) Artificial intelligence assistance for this language. This research gives relevance to the thematic publication on sign languages and to the work done by university institutions in favor of linguistic research on sign languages, which show their commitment to the deaf community.